What Aspects of Formality Do Workers Value? Evidence from a Choice Experiment in Bangladesh - Mahmud, Minhaj (World Bank, Washington, DC, 2020)
This study uses a choice experiment among 2,000 workers in Bangladesh to elicit willingness to pay (WTP) for job attributes: a contract, termination notice, working hours, paid leave, and a pension fund. Using a stated preference method allows calculation of WTP for benefits in this setting, despite the lack of data on worker transitions, and the fact that many workers are self-employed, which makes it difficult to use revealed preference methods. Workers highly value job stability: the average worker would be willing to forego a 27 percent increase in income to obtain a 1-year contract (relative to no contract), or to forego a 12 percent increase to obtain thirty days of termination notice. There is substantial heterogeneity in WTP by type of employment and gender: women value shorter working hours more than men, while government workers place a higher value on contracts than do private sector employees.